TINJAUAN ETIKA BISNIS SYARI’AH TERHADAP PENETAPAN HARGA DALAM JUAL BELI ONLINE (STUDY KASUS ILUKBA SHOP TAMBAKBERAS) - Nurul Laili, Miftasari; Faruq, Ahmad (Irtifaq, 2022)
This article is aimed at describing Sharia business ethics on pricing statement of online trading viewed by Islamic values. Using qualitative research by interview, observation and documentation in collecting the data, the writer analyzed by descriptive method. The results of this study indicate that: in determining the application of pricing there are three components, namely, First, the syariah business ethics, the importance of applying sharia business ethics in buying and selling with the rules that have been listed in its principles. Second, without following the rules of Islamic business ethics principles will affect consumer satisfaction. The author found several consumer dissatisfaction in the service of business actors, namely the delivery of information, admin service and dissatisfaction of goods. And the third difference in pricing at Resellers and Customers.Some suggestions as implications of the results of the study: 1. Hold a discount at the end of the year or at certain moments 2. Management must be tightened again in terms of discipline and trust in customers. Convey information clearly and in detail. 4. Routinely ask customers about satisfaction at the completion of each transaction.Keywords: Sharia business ethics, Pricing, Buying and Selling Online